Spa Culture and Literature in England, 1500-1800
XXXIV, 290 p. 9 illus., 2 illus. in color.
Keywords: This edited collection aims at highlighting the various uses of water in sixteenth, seventeenth, and eighteenth-century England, while exploring the tensions between those who praised the curative virtues of waters and those who rejected them for their supposedly harmful effects. Divided into three balanced sections, the collection includes contributions from renowned specialists of early modern culture and literature as well as rising young scholars as it seeks to establish a dialogue between different methodologies, and explain why the spa-related issues examined still resonate in today’s society. Sophie Chiari is Professor of English Literature at the Université Clermont Auvergne, France, specializing in ecocritical studies. Previous publications include Shakespeare’s Representation of Weather, Climate and Environment (2019). She is currently working on Shakespeare’s Environment: A Dictionary (2021). Samuel Cuisinier-Delorme is a lecturer at the Université Clermont Auvergne where his research focuses on English Literature from the 16th _18th centuries. Samuel lives and works in Vichy, where he is developing research projects on waters and balneology. He is currently planning a seminar on spa literature and is also working on a forthcoming book in French on the same topic, Regards sur le thermalisme européen du Moyen Âge au XIXe siècle (2021).